WhatsApp as part of an EFL programme: participation and interaction. (15th September 2021) - Mackay, Jessica; Andria, Maria; Tragant, Elsa; Pinyana, Àngels
Abstract: This study examines the results of an intervention conducted with adult EFL learners in Barcelona, Spain, to foster engagement with the target language outside class time. As part of the programme, the messaging service WhatsApp was used to carry out a range of voluntary communicative tasks, in learners' own time. Familiarity with this tool made it easy to use, and learner feedback was positive. Analysis of the resulting chat transcript indicated that (1) off-task participation increased as learners appropriated the space as a vehicle for their own communication, (2) off-task interactions fell predominantly into two categories: administrative and social, and (3) despite being voluntary and unevaluated, with minimum teacher intervention, English was overwhelmingly the language of choice within these interactions. We hope this study can serve as an example of the possibilities offered by the WhatsApp medium in an EFL context.